Enlightenment's frontier : the Scottish Highlands and the origins of environmentalism - Jonsson, Fredrik Albritton, 1972- (Lewis Walpole series in eighteenth-century culture and history., 2013)
"This is the first book to explore the environmental foundation of the Scottish Enlightenment. Such a perspective sheds new light on one of the great problems of social theory: What are the causes and limits of economic development? The first part of the book recounts how natural historians turned Highland Scotland into a practical laboratory and internal frontier after 1745. They sought to make northern Scotland into a cornucopia by transforming local ecosystems, soils, and even the climate itself. They also promoted maximum population growth by advocating a new standard of minimal subsistence based on spade husbandry. But these projects provoked political controversy as well as unintended social consequences. The second section shows how conservative and liberal improvers clashed over the fit between the environment and the social order. Adam Smith's defense of free markets presumed an ideal order of self-regulating natural systems whereas his critics stressed the need for human expertise and government to regulate fragile environments. These two rival ecologies of development have left a deep mark on the history of capitalism and conservationism. The final part of the book charts the collapse of the improvement schemes in the north. Now the region became the stage for a political debate about the physical limits to growth, feeding new fears of overpopulation, coal exhaustion and the stationary state. The book thus excavates the idealized vision of nature in Adam Smith's defense of free markets and also reveals how the Scottish Enlightenment helped give birth to modern environmentalism"--